2021
DOI: 10.1002/nau.24759
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and savings, and clinical outcomes of televisits in female pelvic medicine and reconstructive surgery at an urban academic center

Abstract: Aim To evaluate patient satisfaction and savings, and compare visit outcomes based on chief complaint (CC) of women presenting for a televisit to a female pelvic medicine and reconstructive surgery (FPMRS) clinic at an urban academic center. Methods A cross‐sectional study of women completing a televisit with an FPMRS specialist at our institution from June 19, 2020 to July 17, 2020 was conducted. A telephone questionnaire was administered to patients to assess satisfaction and savings (travel costs/time avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous studies have investigated the satisfaction of female patients presenting for a telemedicine visit in a female pelvic medicine clinic. Shin et al 15 performed a cross-sectional study in an urban academic center using a telephone questionnaire. Nearly 90% of patients undergoing telemedicine visits were satisfied with their experience.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the satisfaction of female patients presenting for a telemedicine visit in a female pelvic medicine clinic. Shin et al 15 performed a cross-sectional study in an urban academic center using a telephone questionnaire. Nearly 90% of patients undergoing telemedicine visits were satisfied with their experience.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al (24), in their study, examined the patient contentedness and savings and clinical results of televisits in female pelvic medicine and reconstructive surgery at an urban educational center and identified that the patients reported a variety of savings, such as 88 (48.1%) of them saved at least 1 h in travel time and 54 (28.9%) saved more than $25 on transportation costs. The patient and family burden was reduced because 43 (23%) had a healthcare issue that made it hard to go for face-toface appointments, 37 (19.8%) said that traveling for face-to-face appointments was grueling, and 41 (21.9%) said that doing a televisit allowed them to avoid taking time off work.…”
Section: Benefits Of Telemedicine In Healthcarementioning
confidence: 99%
“…The patient and family burden was reduced because 43 (23%) had a healthcare issue that made it hard to go for face-toface appointments, 37 (19.8%) said that traveling for face-to-face appointments was grueling, and 41 (21.9%) said that doing a televisit allowed them to avoid taking time off work. More than half of all patients 94(51.4%) indicated they generally spend more than half an hour in the waiting area for face-to-face sessions (24).…”
Section: Benefits Of Telemedicine In Healthcarementioning
confidence: 99%
See 2 more Smart Citations